Interphase Nuclear Structure And Heterochromatin Percentages In Somatic Cells On Ten Cultivars Of Lablab Purpureus L. (Journal of Bio-Science, 2024)
Mitotic index of Lablab purpureus was found highest in BARI Sheem-6 and lowest in BARI Sheem-1. A high mitotic index value shows the higher growth patterns of plants than others. The interphase nuclear structure analysis showed differences in the organization and distribution of chromatin within the nuclei of the cultivars. Percentages of heterochromatin were found highest in BARI Sheem-5 and lowest in BARI Sheem-3 which may be considered as more primitive and more advance in nature, respectively. Some cultivars exhibited a more condensed and organized nuclear structure, while others displayed a more dispersed and irregular arrangement of chromatin. Furthermore, the measurement of heterochromatin percentage indicated significant variations among the cultivars. Heterochromatin, which is associated with the gene silencing and genome stability, ranged from low to high percentages in different cultivars. This suggests potential differences in gene expression and genomic stability among the 10 cultivars of L. purpureus. Overall, the study highlights the existence of genetic diversity in L. purpureus cultivars, as evidenced by variations in interphase nuclear structure and heterochromatin percentage. These findings contribute to a better understanding of the genetic and epigenetic factors that influence the phenotypic characteristics agronomic performance of L. purpureus.J. Bio-Sci. 32(1): 13-19, 2024